Análise da ortografia na escrita de alunos surdos do Ensino Superior - Adriana Aparecida de Oliveira (2022)
This research aims to analyze the knowledge and mastery of written skills, more specifically, spelling of deaf students in Higher Education. We hypothesized that these data reflect, in some way, the learning path in basic education and can contribute to a better understanding the errors and difficulties that persist beyond high school. To carry out this research, we take on as a theoretical basis the IMP, Integration of Multiple Templates (TREIMAN; KESSLER, 2014), according to which students use different mechanisms, including morphological and statistical basis, for spelling appropriation. The corpus is composed of data from two types of instrument: a production of texts and a directed writing activity, consisting of an illustrated dictated, of previously selected words, and two open-ended questions involving reflection about spelling. The results show that the main spelling difficulties are related to visual perception and word memory, especially words with more than three syllables, being the most frequent deviation the exchange of segments. We also identified that sign language influences the student's writing, when there is doubt about the meaning or lexical selection. We also found that there is influence of issues related to syllabic permissions and restrictions in Portuguese writing language. Based on the results and also obtained and considering the adopted theory (IMP), we suggest possible practices for teaching spelling, based on the conception of text focused on the visual aspect, mediated by sign language.